2020
DOI: 10.1136/gutjnl-2018-317856
|View full text |Cite
|
Sign up to set email alerts
|

SUMO pathway inhibition targets an aggressive pancreatic cancer subtype

Abstract: ObjectivePancreatic ductal adenocarcinoma (PDAC) still carries a dismal prognosis with an overall 5-year survival rate of 9%. Conventional combination chemotherapies are a clear advance in the treatment of PDAC; however, subtypes of the disease exist, which exhibit extensive resistance to such therapies. Genomic MYC amplifications represent a distinct subset of PDAC with an aggressive tumour biology. It is clear that hyperactivation of MYC generates dependencies that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
107
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(108 citation statements)
references
References 59 publications
1
107
0
Order By: Relevance
“…34 Both ML-792 and ML-93 inhibit the growth of PDAC cells and show a significant correlation in their half-maximal growth inhibitory concentrations in a large panel of murine PDAC cell lines. 22 In sensitive pancreatic cancer models, ML-93 was effective in the double-digit nanomolar range, which was lower than the range observed using ML-792, resulting in the accumulation of cells in the G2/M phase of the cell cycle and in polyploidy with associated apoptosis. 22 These results demonstrate the importance of SUMOylation for proper mitotic progression.…”
Section: Inhibitors Of the Sumo Pathwaymentioning
confidence: 90%
See 3 more Smart Citations
“…34 Both ML-792 and ML-93 inhibit the growth of PDAC cells and show a significant correlation in their half-maximal growth inhibitory concentrations in a large panel of murine PDAC cell lines. 22 In sensitive pancreatic cancer models, ML-93 was effective in the double-digit nanomolar range, which was lower than the range observed using ML-792, resulting in the accumulation of cells in the G2/M phase of the cell cycle and in polyploidy with associated apoptosis. 22 These results demonstrate the importance of SUMOylation for proper mitotic progression.…”
Section: Inhibitors Of the Sumo Pathwaymentioning
confidence: 90%
“…22 In sensitive pancreatic cancer models, ML-93 was effective in the double-digit nanomolar range, which was lower than the range observed using ML-792, resulting in the accumulation of cells in the G2/M phase of the cell cycle and in polyploidy with associated apoptosis. 22 These results demonstrate the importance of SUMOylation for proper mitotic progression. 35 An ML-792/ML-93-derived SAE inhibitor, TAK-981, entered clinical development in 2019, with Phase 1 trials recruiting patients with any advanced or metastatic solid tumour and lymphoma (NCT03648372 and NCT04074330).…”
Section: Inhibitors Of the Sumo Pathwaymentioning
confidence: 90%
See 2 more Smart Citations
“…In addition, many components of the SUMO pathway, including E1, E2, and several PIAS E3 proteins were shown to be highly expressed in both B-cell lymphomas and pancreatic cancer overexpressing c-Myc. This results in higher overall SUMO conjugation and consequent vulnerability of these tumors to inhibition of SUMOylation (Hoellein et al, 2014;Biederstädt et al, 2020). Finally, we have recently shown that the SUMO pathway plays an important role, on one side, in the response of acute myeloid leukemias (AML) to standard chemotherapies (Bossis et al, 2014) and, on the other side, in the resistance of nonpromyelocytic AML to differentiation therapies using retinoic acid (Baik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%